Perceived stress and recovery in overreached young elite soccer players - Brink, M.; Visscher, C.; Lemmink, K. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
A disturbed balance between stress and recovery is considered to be the cause of overreaching. Monitoring the stress recovery balance might prevent athletes from symptoms such as fatigue and disturbed mood, eating and sleeping patterns (Nederhof et al. 2008). Since overreaching is characterized by sport-specific performance decrement (Meeusen et al. 2006), research is needed that relates measures of stress and recovery to performance decrement. Therefore, the goal of this study was to investigate if stress and recovery can be used as a tool to prevent overreaching in elite soccer players. Methods Stress, recovery and performance were prospectively monitored in 94 young elite soccer players during two competitive seasons. The Dutch version of the Recovery Stress Questionnaire for athletes (RESTQ-Sport) was used monthly to assess the stress-recovery state of players (Nederhof et al. 2008). Performance was monthly assessed by means of a submaximal Interval Shuttle Run Test (Lemmink et al. 2004; Brink et al. 2009). Subjects with a heart rate increase = 5 b•min-1 of four up to eight weeks were classified as overreached. A sports physician screened all subjects to exclude other causes of performance decrement. Individual differences in perceived stress and recovery over the previous two months of eleven overreached soccer players and six controls were analysed (mean ± SD: Age (years) 17 ± 1, Height (cm) 176.56 ± 5.33, Weight (kg) 69.50± 6.06). Positive stress scores indicated increased stress, whereas negative recovery scores indicated decreased recovery. Results Mann-Whitney tests showed that there were no significant differences between overreached and control soccer players in general stress (mean± SD: 1.5 ± 4.0 vs. 0.5 ± 1.3), general recovery (-0.7 ± 2.1 vs. 1.2 ± 2.5), sport-specific stress (-0.1 ± 1.5 vs. -0.1 ± 0.3) and sport-specific recovery (0.3 ± 1.9 vs. 0.8 ± 2.6). Discussion The results demonstrate no differences in perceived stress and recovery between overreached and control soccer players. However, there is a tendency that overreached soccer players experience more stress and less recovery. The large standard deviation indicates that some players do not report changes in stress and recovery, despite performance decrement. Possible explanations are the relative young age of the players and different psychosocial awareness of team sport athletes. This should be kept in mind when using these subjective ratings.